MSC virtual e-abstract (NPP) - Stroke Conference 2020, Malaysia (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
Endothelin-1 induced focal ischemia in adult zebrafish: A model with novel entity of stroke research. Poly (lactide-co-glycolide) nanoparticle encapsulating brain-derived neurotrophic factor promotes neuroprotection in an acute ischemic stroke model in the rat. Tele-consultation for augmentative and alternative communication in individuals with locked-in syndrome. Teleneurorehabilitation during covid-19 pandemic in Malaysia. Evaluation of oral health status and salivary parameters among stroke patients in Hospital USM, Kelantan. The neuroprotective effect of (s)-3,5-dhpg preconditioning via down regulatory antagonist modulator (dream) in acute ischemic stroke rats. The effects of hypothermia and p4 on glt-1 and p62 of primary cortical astrocytes following exposure to glutamate toxicity. Assessment of awareness and action towards signs and symptoms of stroke among lay public in Kuantan, Malaysia: A cross-sectional a study.